GE_GERICHTE P/14285/2023 vom 23. Juli 2024 - GE Cour de justice (2024)
MESURE DE SUBSTITUTION À LA DÉTENTION;EXPULSION(DROIT PÉNAL);MESURE THÉRAPEUTIQUE INSTITUTIONNELLE;IRRESPONSABILITÉ;RÈGLEMENT (CE) 1987/2006 | CP.59.al1; CP.66a bis; CP.19